Evolving Clinical Care in Esophageal Button Batteries: Impact of Expert-Opinion Guideline Adoption and Continued Gaps in Care. Issue 2 (February 2022) - Sinclair, Elizabeth M.; Santore, Matthew T.; Agarwal, Maneesha; Kitzman, Jamie; Sauer, Cary G.; Riedesel, Erica L.
ABSTRACT: Background/Objectives: Esophageal button battery impactions (BBI) in children pose a significant danger to children. Although there are expert-opinion guidelines to help manage this population, few studies detail the impact of guidelines on the clinical care of these patients. With this study, we aimed to describe the care of these patients before and following adoption of guidelines at a single center. Methods: Retrospective cohort study of patients with esophageal BBI at a single center, large volume, urban academic pediatric hospital system before adoption of expert-opinion guidelines (2007–2017) and following adoption (2018–2020). Results: Cohort was comprised of 31 patients before adoption and 32 patients following adoption of guidelines. Patient characteristics did not differ between groups. After 2018, significantly more patients received acetic acid irrigation, initial cross-sectional imaging, and serial cross-sectional imaging. There was also an increase in intensive care unit (ICU) stays, number of intubations, nil per os time, and hospital length of stay. There was no difference in patient outcomes. Conclusion: This study describes a large cohort of pediatric esophageal BBI before and following adoption of guidelines. Findings detail increased adherence to guidelines resulting in more cross-sectional imaging which led to ICU stays, longer length of stays, and more nil per os time. This study emphasizes the need for multi-disciplinary guidelines as well as further multi-institutional study. Abstract : Supplemental Digital Content is available in the text